Two cases of congenital vallecular cyst: a reminder of the potentially fatal cause of upper airway obstruction in infants - Abd. Aziz, Azian; Abdullah, Ahmad Fadzil; Raja Lope Ahmad, Raja Ahmad Al'konee (Universiti Sains Malaysia, 2010)
Vallecular cyst, a benign yet rare laryngeal lesion, may cause stridor and even life-threatening upper airway obstruction in infants. It can cause apnoea and poor feeding habits, thus reducing the chance of survival. Although laryngomalacia remains the most common cause of stridor in this age group, awareness and a high level of suspicion for this condition can help lead to early management and intervention. Direct laryngoscopy is accepted as the gold standard for diagnostic purposes, and marsupialisation of the cyst is the preferred treatment. We describe 2 cases of vallecular cysts in infants admitted to our hospital where timely diagnoses led to appropriate treatment.